Determinant of Trade Balance: Empirical Study in ASEAN 5 Countries - Erika Novendira Purnamasari; Idah Zuhroh; Eris Tri Kurniawati (Jurnal Ekonomi Pembangunan, 2022)
International trade is a form of partnership and global activity of a country with other countries, traded from exports and imports. International trade activity is recorded in the trade balance for a certain period based on the value of the prevailing currency. It is one of the benchmarks for the success of an economy. This study examines the relationship between fundamental macroeconomic variables consisting of inflation, interest rates, imports, exchange rates, and GDP, which affect the trade balance performance in ASEAN-5 (Indonesia, Malaysia, Philippines, Singapore, and Thailand). The analytical method used is a regression with panel data from 2000-2019 with research objects from ASEAN-5 countries. The results of the analysis found that interest rates and imports had a significant adverse effect on the trade balance in ASEAN-5. GDP and exchange rates significantly positively affect the trade balance of ASEAN-5 countries. On the other hand, inflation has a negative effect but does not significantly affect the trade balance in ASEAN-5 countries.